Intravital FLIM-FRET imaging reveals dasatinib-induced spatial control of src in pancreatic cancer - Nobis, Max; McGhee, Ewan J; Morton, Jennifer P; Schwarz, Juliane P; Karim, Saadia A; Quinn, Jean; Edward, Mike; Campbell, Andrew D; McGarry, Lynn C; Evans, T R Jeffry; Brunton, Valerie G; Frame, Margaret C; et al. (Cancer research (Chicago, Ill.), 2013)
Cancer invasion and metastasis occur in a complex three-dimensional (3D) environment, with reciprocal feedback from the surrounding host tissue and vasculature-governing behavior. In this study, we used a novel intravital method that revealed spatiotemporal regulation of Src activity in response to the anti-invasive Src inhibitor dasatinib. A fluorescence lifetime imaging microscopy-fluorescence resonance energy transfer (FLIM-FRET) Src biosensor was used to monitor drug-targeting efficacy in a transgenic p53-mutant mouse model of pancreatic cancer. In contrast to conventional techniques, FLIM-FRET analysis allowed for accurate, time-dependent, live monitoring of drug efficacy and clearance in live tumors. In 3D organotypic cultures, we showed that a spatially distinct gradient of Src activity exists within invading tumor cells, governed by the depth of penetration into complex matrices. In parallel, this gradient was also found to exist within live tumors, where Src activity is enhanced at the invasive border relative to the tumor cortex. Upon treatment with dasatinib, we observed a switch in activity at the invasive borders, correlating with impaired metastatic capacity in vivo. Src regulation was governed by the proximity of cells to the host vasculature, as cells distal to the vasculature were regulated differentially in response to drug treatment compared with cells proximal to the vasculature. Overall, our results in live tumors revealed that a threshold of drug penetrance exists in vivo and that this can be used to map areas of poor drug-targeting efficiency within specific tumor microenvironments. We propose that using FLIM-FRET in this capacity could provide a useful preclinical tool in animal models before clinical translation.